2011
DOI: 10.1177/1090198111407185
|View full text |Cite
|
Sign up to set email alerts
|

Physician Knowledge and Awareness of CA-125 as a Screen for Ovarian Cancer in the Asymptomatic, Average-Risk Population

Abstract: Effective early detection strategies for ovarian cancer do not exist. Current screening guidelines recommend against routine screening using CA-125 alone or in combination with transvaginal ultrasonography (TVS). In this study, the authors used the 2008 DocStyles survey to measure clinician beliefs about the effectiveness of CA-125 and TVS in the asymptomatic, average-risk population in the United States. To assess the need for provider education, the authors used the 2008 HealthStyles survey to examine public… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…This study showed that about 25% of women reported having heard of the CA-125, with about 10% of women reporting having previously received a CA-125 blood test. 24 Characteristics of women who had not heard of or had the CA-125 blood test were similar to those who had, with the exception that those who had heard of it/had it were more often older and perimenopausal or postmenopausal. 24 Concern for getting ovarian cancer did not differ significantly among women who heard of/had the CA-125 test compared to those who had not heard of or had it.…”
Section: Additional Research To Inform the Campaignmentioning
confidence: 81%
See 3 more Smart Citations
“…This study showed that about 25% of women reported having heard of the CA-125, with about 10% of women reporting having previously received a CA-125 blood test. 24 Characteristics of women who had not heard of or had the CA-125 blood test were similar to those who had, with the exception that those who had heard of it/had it were more often older and perimenopausal or postmenopausal. 24 Concern for getting ovarian cancer did not differ significantly among women who heard of/had the CA-125 test compared to those who had not heard of or had it.…”
Section: Additional Research To Inform the Campaignmentioning
confidence: 81%
“…24 Characteristics of women who had not heard of or had the CA-125 blood test were similar to those who had, with the exception that those who had heard of it/had it were more often older and perimenopausal or postmenopausal. 24 Concern for getting ovarian cancer did not differ significantly among women who heard of/had the CA-125 test compared to those who had not heard of or had it. 24 A third analysis from the same survey data examined self-reported intent to seek care for symptoms associated with ovarian cancer.…”
Section: Additional Research To Inform the Campaignmentioning
confidence: 81%
See 2 more Smart Citations
“…Currently there are two tests being used for ovarian cancer screens, transvaginal ultrasound (TVUS) and measurement of blood levels of CA-125 protein (7)(8)(9). TVUS may only detect tumours of a certain mass and as such is not effective for very early stages of cancer development nor for differentiating between HGSC and SBT.…”
Section: Introductionmentioning
confidence: 99%